STUDY OF TRANSFORMATIONAL LEADERSHIP AND TEACHER COMMITMENT IN PUBLIC SCHOOL REFORM - Musa, Khalip (International Business Education Journal, 2014)
This study was designed to examine the relationship between transformational and transactional leadership styles and their influence on teachers’ commitment from the perspective of teachers in selected public primary schools reform. This study sought to examine the degree to which these leadership styles managed to influence levels of teacher commitment. The researcher surveyed 285 teachers from four primary schools to study the relationship between transformational and transactional leadership and commitment using the multifactor leadership questionnaire (Bass & Avolio, 2004) and the three-component model of employee commitment survey (Meyer & Allen, 1997). The findings indicated that transformational leadership had a significant influence on teachers’ commitment, whereas no significant influence on teachers’ commitment was found as a result of transactional leadership.